Body shape concerns across racial and ethnic groups among adults in the United States: More similarities than differences. (December 2020) - Olson, KayLoni L.; Lillis, Jason; Panza, Emily; Wing, Rena R.; Quinn, Diane M.; Puhl, Rebecca R.
Highlights: The relationship between race and body image remains incompletely understood. This large sample was racially diverse with men and women of varying body sizes. Findings reveal more similarities in body shape concerns across race/ethnic groups. The association of BMI and body shape concerns differs by gender. Abstract: This study evaluated the relationship between race/ethnicity and body shape concerns among adults in the U.S. and evaluated if this relationship varied by Body Mass Index (BMI) and gender. Data were collected from U.S. adults (N = 2, 212) using a national online survey panel designed to approximate the US census data. Gender, age, race/ethnicity, BMI and body shape concerns (Body Shape Questionnaire) were assessed. Analysis of variance was utilized to evaluate the race/ethnicity and BSQ association and if the relationship varied by gender and BMI category. The sample (65 % White, 13 % Black/African American, 16 % Latino/Hispanic/Mexican American and 6 % Asian/Pacific Islander) was 50 % female; mean age of 44.2 years ( SD = 16.8); BMI of 27.4 ( SD = 6.7). A gender by BMI category interaction ( p < .01) revealed no difference in BSQ scores by gender when BMI < 18, but higher BSQ scores among women for all other BMI groups. A main effect of race/ethnicity revealed BSQ scores were equally high across racial/ethnic groups, except individuals who identified as White (M = 42.0, SD = 19.7) reported higher BSQ than those identified as Asian/Pacific Islander (M = 37.4, SD = 17.4). Body shape concerns are common among US adults. Individuals of racial/ethnic minority status may experience similar gender- and BMI-related differences in body shape concerns as White individuals.